Kreatifitas Guru Mendesain Pembelajaran: Kajian Fenomenologi Dalam Pembelajaran Daring Pada Masa Pandemi Covid-19 - Fitrotul Mufaridah; Topo Yono; M. Fikrul Ikhtiar; Pandhutama Raharjo (Indonesian Journal of Educational Science (IJES), 2022)
Learning during the Covid-19 pandemic was designed by teachers who were often considered abnormal because it was different from learning activities during normal times. Both teachers and students experience obstacles in carrying out learning, both offline and online. For this reason, this study aims to describe how the learning phenomenon during the Covid-19 pandemic in Bangkalan Madura, and how the teacher's creativity is in designing learning. Data collection was carried out through questionnaires, interviews, and observation of learning design documents carried out during the pandemic. This study used a qualitative descriptive analysis of Miles and Huberman. The results of this study indicate that there are two different phenomena of changes in the form of learning implementation and creative learning designs carried out by two teachers from different schools in Bangkalan Madura. Changes in form occur referring to the accessibility aspect of the implementation of learning by paying attention to the obstacles faced by both teachers and students. This change in form provides teachers with literacy challenges, both digital literacy, and creativity. This research proves that teachers' creativity in realizing 21st-century learning in this pandemic has become increasingly sharp. Two phenomena of changing the form of learning implementation and the creativity of learning designs carried out by teachers during this pandemic can be examples or references for other teachers in carrying out blended learning or online learning during the pandemic.